Body composition as a predictor of chemotherapy-related toxicity in pancreatic cancer patients: A systematic review - Rizzo, Stefania; Scala, Isabel; Robayo, Angela Rodriguez; Cefalì, Marco; De Dosso, Sara; Cappio, Stefano; Xhepa, Genti; Del Grande, Filippo (Frontiers in Oncology, 2022)
Objectives The objective of this systematic review was to assess associations between quantitative body composition measures extracted from imaging examinations and chemotherapy-related toxicity in pancreatic cancer patients. A secondary objective was to evaluate the different definitions of sarcopenia across included studies. Methods This systematic review was conducted according to the PRISMA statement. A comprehensive literature search of three electronic databases was performed by two authors. For each eligible article, information was collected concerning the clinical setting; basic study; population characteristics; technical; body composition features evaluated; CA 19.9 tumor marker levels; chemotherapy drugs administered; toxicities (hematologic, nausea/vomiting, diarrhea, neuropathy, reduction of number of cycles, overall toxicity); association of body composition values with toxicities. The overall quality of the included studies was critically evaluated. Results After the initial retrieval of 1137 articles, the systematic review included 12 articles (1/12 in the neo-adjuvant setting; 2/12 in the adjuvant setting; 3/12 in the metastatic setting; 2/12 in the unresectable setting; the other 4/12 included more than one clinical setting). The number of patients included ranged between 17 and 251; mean/median age ranged between 63 and 77 years; the percentage of sarcopenic patients ranged between 23 and 76%. The most frequent body composition parameter evaluated was skeletal muscle index (11/12). Chemotherapy regimens included gemcitabine (as monotherapy or in combination with other drugs); FOLFIRINOX and S-1. Among the trials including gemcitabine, 2/9 demonstrated an association with toxicity, whereas 7/9 did not; among those including FOLFIRINOX, one demonstrated associated toxicity whereas the others did not. Altogether, 4/12 papers demonstrated an association between the body composition values and the development of chemotherapy-related toxicities. Conclusions There is a wide variability of results about the association of body composition and chemotherapy-related toxicity in PC patients. Furthermore, cut-off values to define sarcopenia in PC patients are not yet uniformly defined. Systematic Review Registration https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42022337753, identifier CRD42022337753.